Computational dosimetry and post-irradiation studies of the electron beam irradiation-assisted corrosion and stress corrosion cracking of statically strained steel samples in a supercritical water coolant - Bakai, O.S.; Boriskin, V.M.; Bratchenko, M.I.; Dyuldya, S.V. (Вопросы атомной науки и техники, 2022)
New experimental data on the corrosion behavior of the 12X18H10T austenitic steel elastically strained cou-pons after 500 h long exposure in situ the NSC KIPT “Electron Irradiation Test Facility” supercritical water circulation loop are presented and discussed. The γ-activation analysis based computational dosimetry of samples is correlated to their weight gain/loss measurement data. The absorbed dose and stress effect on their irradiation assisted general corrosion is revealed. The corrosion surface/layer chemistry/microstructure are discussed with special emphasis of the irradiation/stress impact on the protective coating stability, intergranular corrosion and precursors of cracking. Наведені та обговорюються нові експериментальні дані щодо корозійної поведінки пружно деформованих купонів аустенітної сталі 12X18H10T після 500-годинної експозиції in situ надкритичної водної конвекційної петлі установки «Electron Irradiation Test Facility» ННЦ ХФТІ. Засновані на γ-активаційному аналізі дані обчислювальної дозиметрії зразків зіставлені з даними вимірів набуття або втрати їх маси. Виявлений вплив поглиненої дози та напруги на їх стимульовану опроміненням загальну корозію. Склад та мікроструктура корозійної поверхні та шару обговорюються з особливою увагою до впливу опромінення й напруги на стабільність захисного покриття, міжзеренну корозію та передвісники розтріскування. Приведены и обсуждаются новые экспериментальные данные по коррозионному поведению упруго-деформированных купонов аустенитной стали 12X18H10T после 500-часовой экспозиции in situ сверхкритической водной конвекционной петли установки «Electron Irradiation Test Facility» ННЦ ХФТИ. Основанные на γ-активационном анализе данные вычислительной дозиметрии образцов сопоставлены с данными измерений набора или потери ими массы. Выявлено влияние поглощенной дозы и напряжения на их стимулированную облучением общую коррозию. Состав и микроструктура коррозионной поверхности и слоя обсуждаются с особым вниманием к влиянию облучения и напряжения на стабильность защитного покрытия, межзеренную коррозию и предвестники растрескивания.